Republican Orators from Eisenhower to Trump (Rhetoric, Politics and Society, 2018)
This is the first thorough and systematic interrogation of Republican Party oratory and rhetoric that examines a series of leading figures in American conservative politics. It asks: How do leading Republican Party figures communicate with and influence their audiences?; What makes a successful speech, and why do some speeches fail to resonate? Most importantly, it also investigates why orators use different styles of communication with different audiences, such as the Senate, party conventions, public meetings, and through the media. By doing so it shines important new light into conservative politics from the era of Eisenhower to the more brutal politics of Donald Trump. The book will appeal to students and scholars across the fields of US politics, contemporary US history, and rhetoric and communication studies.